A bi-dimensional classification and characterization of enterprise social media users. Issue 1 (10th May 2021) - Kirchner, Kathrin; Jørgensen, Rasmus; Bolisani, Ettore; Scarso, Enrico
Abstract : Purpose: Enterprise social media (ESM) platforms are rapidly diffusing in the business context because they can bring substantial benefits to companies by enhancing their knowledge management (KM) processes. However, such benefits materialize only if active employee participation is ensured. Therefore, it is crucial to understand how individual employees use an ESM platform to assist their knowledge-related activities. This paper contributes to this topic by proposing a classification of ESM users based on two dimensions: frequency and type (active or passive) of use. Design/methodology/approach: The paper presents the results of a survey of 262 employees of an international engineering service company that has adopted an ESM platform to support its KM processes. Statistical methods (e.g. ANOVA, Tukey's b) were applied to verify the usefulness of the proposed typology and identify the main aspects that characterize the different user groups. Findings: The survey results confirm the existence of different types of ESM users and provide the empirical basis for developing a bi-dimensional classification from which four user groups were derived and characterized: frequent contributors, sporadic contributors, frequent lurkers and sporadic lurkers. Research limitations/implications: The main limitation is that only one company in one sector with specific knowledge needs and capabilities was investigated. Practical implications: The study provides useful suggestions for how to promote the use of an ESM and particularly for how to encourage less frequent and less active users to increase their participation in a platform. Originality/value: The paper contributes to a better understanding of how employees approach ESM by identifying factors that characterize different user groups.